2022
DOI: 10.3389/fcvm.2022.731376
|View full text |Cite
|
Sign up to set email alerts
|

HSP60-Derived Peptide as an LPS/TLR4 Modulator: An in silico Approach

Abstract: As a part of innate immunity mechanisms, the Toll-like receptor (TLR) signaling pathway serves as one of the mainstay lines of defense against pathogenic microorganisms and cell dysfunction. Nevertheless, TLR overactivation induces a systemic proinflammatory environment compromising organ function or causing the patient’s death. TLRs modulators, specially those focused for TLR4, remain a promising approach for inflammatory diseases treatment, being peptide-based therapy a trendy approach. Heat shock protein 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…For this reason, cellular levels of HSPs may increase in heatstroke conditions (as previously discussed) while remaining low in the absence of stressors. Therefore, HSPs play a major role in the biological response to stress, and its modulation and understanding is of interest in diverse pathologies [ 93 , 94 ].…”
Section: Heat Shock Proteins and Sirtuins As Renal Biomarkers Of Prot...mentioning
confidence: 99%
“…For this reason, cellular levels of HSPs may increase in heatstroke conditions (as previously discussed) while remaining low in the absence of stressors. Therefore, HSPs play a major role in the biological response to stress, and its modulation and understanding is of interest in diverse pathologies [ 93 , 94 ].…”
Section: Heat Shock Proteins and Sirtuins As Renal Biomarkers Of Prot...mentioning
confidence: 99%
“…Recently, an Hsp60-derived peptide was also tested in a silico model as a protective tool against inflammation [82]. Previously published results, dating back to 1996, showed that the Hsp60 peptide p277 was able to arrest autoimmune diabetes induced by the toxin Streptozotocin [83].…”
Section: Hsp60-based Therapy and Potential Implication In Alzheimer's...mentioning
confidence: 99%
“…During endotoxic signalling, the Phe126 residue in the hydrophobic pocket of MD-2 represents the "molecular switch". This residue is linked to TLR4 activation and allosterically triggers a conformational shift in a ligand-dependent way [185,186]. Others have reported that during activation of TLR4 via endotoxin, Phe121, Phe126 and Tyr131, played a crucial role in human MD-2 [187].…”
Section: Predicted Interaction Of Fucoidan With Receptors Inhibition ...mentioning
confidence: 99%